Mathematical optics : classical, quantum, and computational methods - Lakshminarayanan, Vasudevan; Calvo, María L.; Alieva, Tatiana (CRC Press, Taylor & Francis Group, 2013)
Going beyond standard introductory texts, Mathematical Optics: Classical, Quantum, and Computational Methods brings together many new mathematical techniques from optical science and engineering research. Profusely illustrated, the book makes the material accessible to students and newcomers to the field. Divided into six parts, the text presents state-of-the-art mathematical methods and applications in classical optics, quantum optics, and image processing. Part I describes the use of phase space concepts to characterize optical beams and the application of dynamic programming in optical wave.